Hydrostatic Chandra X-ray analysis of SPT-selected galaxy clusters – I. Evolution of profiles and core properties. Issue 1 (27th October 2017) - Sanders, J. S.; Fabian, A. C.; Russell, H. R.; Walker, S. A.
Abstract: We analyse Chandra X-ray Observatory observations of a set of galaxy clusters selected by the South Pole Telescope using a new publicly available forward-modelling projection code, mbproj2, assuming hydrostatic equilibrium. By fitting a power law plus constant entropy model we find no evidence for a central entropy floor in the lowest entropy systems. A model of the underlying central entropy distribution shows a narrow peak close to zero entropy which accounts for 60 per cent of the systems, and a second broader peak around 130 keV cm^2 . We look for evolution over the 0.28–1.2 redshift range of the sample in density, pressure, entropy and cooling time at 0.015 R 500 and at 10 kpc radius. By modelling the evolution of the central quantities with a simple model, we find no evidence for a non-zero slope with redshift. In addition, a non-parametric sliding median shows no significant change. The fraction of cool-core clusters with central cooling times below 2 Gyr is consistent above and below z = 0.6 (∼30–40 per cent). Both by comparing the median thermodynamic profiles, centrally biased towards cool cores, in two redshift bins, and by modelling the evolution of the unbiased average profile as a function of redshift, we find no significant evolution beyond self-similar scaling in any of our examined quantities. Our average modelled radial density, entropy and cooling-time profiles appear as power laws with breaks around 0.2 R 500 . The dispersion in these quantities rises inwards of this radius to around 0.4 dex, although some of this scatter can be fitted by a bimodal model.